Lung adenocarcinoma during pregnancy: clinical case and literature review. (2nd October 2019) - Bellido, C.; Barbero, P.; Forcén, L.; Blanco, M.; Alonso-Riaño, M.; Galindo, A.
Abstract: Lung cancer during pregnancy is a very rare disease with less than 70 cases published to date. Information about specific lung cancer as adenocarcinoma is even more limited. Genetic techniques can detect oncogene mutations which seem to be more frequent among cases of lung cancer in pregnant women and could determine both the treatment and prognosis. We present a recent case seen at our hospital and a literature review.